La falta de aplicabilidad del divorcio unilateral en la legislación ecuatoriana no permite tener un trámite ágil y eficaz - Cuenca Erazo, Ana Cristina (2022)
THE UNILATERAL DIVORCE IN THE ECUADORIAN LEGISLATION DOES NOT ALLOW TO HAVE AN AGILE AND EFFICIENT PROCEDURE", the interest to develop this topic is due to the need to incorporate a new model of divorce in a unilateral way that only with the will of one of the spouses can be terminated the marital bond that once united them in marriage. The study shows the difficulties that arise in our country when filing for divorce, this legal institution allows the dissolution of the marriage bond, either by the two types of divorce that exist, the Divorce by Mutual Consent, which is agreement of the wills between the two spouses; and the Divorce Controversy which is the one that is necessary to invoke some cause established in article 110 of the Civil Code, to end the marriage bond, the latter characterized by the delay due to the extensive procedural burden that exist in the courts, which in many cases violating principles and rights. Currently in several legislations of some countries such as Mexico, Nicaragua and Sweden have chosen to incorporate in their legal system, a new type of divorce in which it is based that one of the two parties can terminate the marriage legally, so it is not necessary to invoke or justify any cause, this type of divorce is known as unilateral, binding or uncaused divorce. Therefore, for this Curricular Integration Work, materials and methods were applied that allowed the development of the research, as well as interviews and surveys were carried out with free practicing law professionals, whose results served to propose the project of legal reform to the Civil Code, with the purpose of incorporating a new model of divorce unilaterally, without the need to invoke or require a cause of action.